Treatment with nitric oxide preserves the quality of cold stored ‘cripps pink’ apples - Miqueloto T.* (2021)
© 2021, Agronomic Institute of Campinas. All rights reserved.The objective of this work was to evaluate the effect of pre-storage fruit treatment with nitric oxide (NO) on the quality maintenance of cold stored ‘Cripps Pink’ apples. The following treatments were evaluated: 0 µL·L–1 of NO (control); 10 µL·L–1 of NO for 2 h; 10 µL·L–1 of NO for 4 h; 10 µL·L–1 of NO for 8 h; and 20 µL·L–1 of NO for 2 h. Fruit treated with NO, regardless of concentration and application time, had a greener skin background color than the control, especially those treated with 10 µL·L–1 for 8 h. After 7 days of shelf life (23 ± 3 °C/relative humidity, RH, of 65 ± 5%), fruit treated with 10 µL·L–1 for 8 h and 20 µL·L–1 for 2 h had lower respiration rate and a greener skin background color than the control. Fruit treated with NO, regardless of concentration and application time, had a lower incidence of flesh browning after storage. The use of NO (10 µL·L–1 applied for 8 h and 20 µL·L–1 applied for 2 h) pre-storage maintains the quality of ‘Cripps Pink’ apples, because it delays skin yellowing and reduces flesh browning. Nitric oxide has no effect on the maintenance of flesh firmness in ‘Cripps Pink’ apples.